A literatura de testemunho na américa latina como elemento de ressignificação da memória, da dor e do trauma - Haiski, Vanderléia de Andrade (2021)
The objective of this dissertation is to analyze the Latin American testimonial reports Tejas Verdes: diario de un campo de concentración en Chile (1974), by the Chilean Hernán Valdés, La escuelita: relatos testimoliales (1984), by the Argentinian Alicia Partnoy, Memórias do esquecimento: os segredos dos porões da ditadura (1999), by the Brazilian Flávio Tavares, and El furgón de los locos (2001), by the Uruguayan Carlos Liscano, paying attention to the relationship between the problematic constitution of the witnesses of these narratives, the trauma that marked each one of them, and the relevance of these texts to alleviate the victims' pain, based on the notions of authoritarianism, violence, and trauma. Among the specific objectives of this research, the following ones stand out: to outline the characteristics of testimony in Latin America; to study the differences and the similarities between testimonial and historical accounts; to analyze the impact of trauma on the subjective constitution of the witnesses of the works that constitute the corpus of this project; to examine the relationship between the formal constitution of the books and the Latin American context of the second half of the 20th century; to evaluate the role of such narratives to resignify traumas. The main argument of this research is that, when the survivor writes, he/she transfers part of the traumatic experience and its symptoms to the narrative, and, therefore, gives a new meaning to the history, pain, and memories of the past, and also alleviates the traumatic charge originated from sufferings related to the dark period of the Latin American dictatorships. The research is bibliographically based. In this sense, elements of literary theory from comparative literature, joining interdisciplinary perspectives with other areas of knowledge, are considered for the purpose of the research. Bruno Bettelheim, Cathy Caruth, Dori Laub, Jaime Ginzburg, Néstor Braunstein, Márcio Seligmann-Silva, Marcelo and Maren Viñar, Renato Franco, Shoshana Felman, Sigmund Freud, Theodor Adorno, and Walter Benjamin are the main scholars who underscore the present approach.